STUDYING THE HISTORY OF BUILDING A GOOD SOCIETY IN THE SPIRITUAL HERITAGE OF FAROBI AND IBN SINO (TAMADDUN NURI JURNALI, 2025)
This article is dedicated to analyzing the spiritual heritage of the great thinkers Farabi and Ibn Sina, exploring their views on the virtuous society from a historical perspective. In his work The Virtuous City, Farabi provides a profound philosophical analysis of the principles of establishing an orderly society based on justice, knowledge, and morality. Ibn Sina emphasizes the importance of education and upbringing, highlighting their decisive role in shaping a virtuous society through moral and intellectual advancement. The article examines the significance of these thinkers' views in the development of social-philosophical thought in the medieval Muslim East, the role of knowledge and morality in building a virtuous society, and the influence of their ideas on subsequent philosophical heritage.